The Digital Economy Matters for GTFP: Evidence from Regions in Indonesia - Melisa Octora; Khoirunurrofik Khoirunurrofik (Institut Bisnis dan Informatika Kesatuan, 2026)
The advancement of the digital economy has transformed productivity patterns and created opportunities to support sustainable development, with Green Total Factor Productivity (GTFP) serving as a key indicator that incorporates resource efficiency and environmental considerations. This study aims to examine the effect of the digital economy on GTFP. This study used a multi-year panel dataset, where GTFP is measured through the Malmquist–Luenberger Productivity Index with a Slack-Based Measurement Data Envelopment Analysis (SBM-DEA) approach, and the impact of the digital economy is analyzed using a Two-Way Fixed Effect regression model. The findings show that the digital economy has a significant positive effect on GTFP, with stronger impacts in more developed regions. These results indicate that digital economic development can enhance green productivity by improving human capital and supporting environmentally oriented economic activities. Therefore, policies that integrate digital transformation, human development, and environmental regulation are essential to maximize sustainable productivity and strengthen progress toward long-term sustainable development goals.